EFFECTS OF AGRICULTURAL COMMERCIALIZATION ON POVERTY STATUS OF SMALLHOLDER CASSAVA FARMING HOUSEHOLDS IN OYO STATE, NIGERIA - Jamiu Ayomide HUSSAYN; Dominic Midawa GULAK; Kazeem Oriyomi ABOABA; Oluwadayo Olusola KESHINRO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Transforming the subsistence-oriented cassava production system into a market-oriented production system as a way of increasing the smallholder farmers' income, reducing poverty and thus increasing their welfare has been a policy focus in Nigeria. The study examined the effects of agricultural commercialization on poverty status of smallholder cassava farming households. Multistage sampling procedure was used to select 189 households; data were collected with the use of a well-structured questionnaire and analysed with the use of household commercialization index, FGT index, ordered probit model and logistic regression model. The result of household commercialization index revealed that larger proportion of the farmers commercialize at a high level. Level of education, farming experience, farm income, quantity of cassava produced and extension visits influenced commercialization. The results further showed that 37.28% of smallholder cassava farming household were poor. Sex, level of education, farming experience, quantity of cassava produced, farm income, level of commercialization and extension visit significantly influenced poverty status. The study concludes that most cassava farmers have a high level of commercialization which has a positive influence on the farmers’ welfare. The study recommends farmers’ education, effective policy intervention and programmes on commercialization and access to credit to improve farmers welfare.